مقسم بہ کے انتخاب کےلحاظ سے قرآنی قسموں کی معنویت مُنْتَخَب تفسیری ادب کی روشنی میں تحقیقی وتجزیاتی مطالعہ: Wisdom of Quanic oaths in selección of Muqsam Bihee: A researching and analytical study in the light of Tafseery Literature - Hafiz Nisaar Mustafa (MEI, 2023)
Verily the holy Quran consists on marvelous, unparalleled and unique style in selecting the most suitable MUQSAM BIHEE (مقسم به the personality whom or the thing of which, oath is undertaken). As the Holy Quran was revealed in Arabic, so according to the Arabs, Allah Almighty undertook the oath of the most suitable personality or thing on account of rational aspects emphatic reasons, firmness purpose, peremptory cause, rhetoric motive and to show the dignity and excellence of MUQSAM BIHEE(مقسم به).